1982
DOI: 10.1159/000173498
|View full text |Cite
|
Sign up to set email alerts
|

On the Reliability of Systolic Time Intervals

Abstract: With the purpose of detecting spontaneous variation of systolic time intervals (STI), 20 normal subjects have been examined and the STI has been recorded for 5 consecutive days at the beginning of the test and 20, 40 and 60 min afterwards. Significant differences were found for PEP, LVET and the PEP/LVET ratio between observations (p < 0.05) and between days (p < 0.01). All the values of the STI at the fifth day are rather near the values recorded at the last observation of the first day. This may be related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The best evidence so far comes from a study in 13 female undergraduate students (21) that showed a high correlation (0.82) between absolute PEP and heart period increases in response to sympathetic blockade. In further support, a significant inverse correlation between a subjects' absolute PEP and their plasma adrenaline level was found (48). Endurance athletes showed longer PEP than untrained controls (49).…”
Section: Discussionmentioning
confidence: 68%
“…The best evidence so far comes from a study in 13 female undergraduate students (21) that showed a high correlation (0.82) between absolute PEP and heart period increases in response to sympathetic blockade. In further support, a significant inverse correlation between a subjects' absolute PEP and their plasma adrenaline level was found (48). Endurance athletes showed longer PEP than untrained controls (49).…”
Section: Discussionmentioning
confidence: 68%
“…It might be important to appreciate the day-to-day variation of the systolic time intervals even in patients with stable chronic heart disease. Levi et al (1982) demonstrated the sponraneous variation of systolic time intervals between observations and between days. They smssed the necessity of control groups mated with placebo to evaluate the pharmacological effects on the systolic time intervals.…”
Section: Discussionmentioning
confidence: 92%
“…The exercise values of STI were uncorrected for HR because these corrections would mask the inotropic effect. There was evidence against this practice (Levi et al 1982; Pigott et al 1971; Spodick and Quarry-Pigott 1973; Whitsett and Naughton 1971). …”
Section: Methodsmentioning
confidence: 99%